Influence of weathering on the mechanical strength and factor of safety of andesitic rocks in the Gunung Geulis area, Jatinangor, West Java, Indonesia - Shah, Bilal; Muslim, Dicky; Sophian, Raden Irvan (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Weathering gradually alters the physical character and engineering performance of volcanic rocks, including andesite, which is commonly found and frequently used for construction and slope-related works within the Gunung Geulis region of Sumedang Regency, Indonesia. To examine how these changes affect mechanical behavior, this study compared the estimated uniaxial compressive strength (UCS) and the resulting factor of safety (FOS) of andesite across different weathering grades. Seventy-eight samples were collected from three geological segments, representing slightly to moderately weathered (Grade II–III) and highly weathered (Grade IV). Point Load Tests (PLT) were performed on all samples, and the resulting indices were converted to estimated UCS values using an empirical correlation. Statistical analyses, including descriptive analysis, the Mann–Whitney test, and two-factor analysis, were performed to assess strength differences between weathering grades and geological segments. These estimated UCS values were then converted into shear-strength parameters through the Generalized Hoek–Brown approach, and the corresponding cohesion and internal friction angle were obtained using RocLab 1.0 software for slope-stability modelling in Slide2. The results show a consistent and marked decline in strength as weathering progresses; overall, the estimated UCS decreases by 59.22% across all investigated segments, demonstrating that increasing weathering reduces the rock strength by more than half. This reduction in rock-mass strength is reflected in the slope-stability analyses, where slopes composed of SW–MW andesite produced FOS values ranging from 3.518 to 4.271, indicating relatively stable slope conditions, whereas HW andesite yielded lower FOS values ranging from 1.191 to 1.307, representing comparatively lower and marginally stable conditions. These findings demonstrate that progressive weathering significantly reduces the mechanical performance and slope stability of andesitic rock in the Gunung Geulis area.